Centros de ciencia en Colombia: intercambio de conocimiento tácito entre los mediadores y el público en la comunicación de la ciencia (2021)
This paper presents evidence of the tacit knowledge of mediators when they communicate science from the variables of organizational culture, personal qualities, and dimensions intended to exchange knowledge. To obtain the certainties of the know-how of the mediators, we used face-to-face interviews, and thus defined the different categories. The explicitness of tacit knowledge serves as a guide for the design of strategies that strengthen the training of individuals and encourage citizen learning. The science centers that participated in the research were Maloka, Planetario Distrital, Jardín Botánico de Medellín, and Jardín Botánico de Bogotá. Finally, some considerations are presented on the value of the codification of tacit knowledge, which until then had been difficult to share as it remained deeply and uniquely rooted in people's minds, and, therefore, invisible, but that now emerges and serves as an input for the management of the Science Centers through mediation.